2021
DOI: 10.33585/cmy.73101
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and bioactivity of endolichenic fungi in Usnea lichens of the Philippines.

Abstract: Endolichenic fungi (ELF; asymptomatic microorganisms living inside healthy lichen thalli) were isolated from three Usnea species, namely U. baileyi, U. bismolliuscula and U. pectinata, collected near the town of Sagada, Philippines. A total of 101 ELF were recovered representing 12 genera (classes Sordariomycetes and Eurotiomycetes), with the genera Nemania (50.5%, 51 isolates) and Xylaria (22.8%, 23 isolates) being the most abundant.Comparative analyses on the antimicrobial activities of lichens and ELF revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Galinato et al [35] recently reported that ELF could be leading producers of antioxidants within the lichen thalli, since ELF crude culture extracts exhibited stronger antioxidant activities than the crude lichen extracts. Similar results were reported by Santiago et al [36]. It is, thus, possible that ELF protects the host against harmful conditions through the production of reactive oxygen species (ROS).…”
Section: Endolichenic Fungi (Elf) and Their Role In The Lichen Symbiosissupporting
confidence: 84%
See 2 more Smart Citations
“…Galinato et al [35] recently reported that ELF could be leading producers of antioxidants within the lichen thalli, since ELF crude culture extracts exhibited stronger antioxidant activities than the crude lichen extracts. Similar results were reported by Santiago et al [36]. It is, thus, possible that ELF protects the host against harmful conditions through the production of reactive oxygen species (ROS).…”
Section: Endolichenic Fungi (Elf) and Their Role In The Lichen Symbiosissupporting
confidence: 84%
“…Interestingly, in addition to the biopharmaceutical applications mentioned above, some of the ELF metabolites were also tested for their agricultural potential such as nematicidal [69], biocontrol [70], and phytotoxic activities [71,72]. In the Philippines, the first reports of ELF were that of Galinato et al [35], Santiago et al [36], and Tan et al [44]. Galinato and colleagues isolated 11 morphologically distinct ELF from the fruticose lichen, Ramalina peruviana, collected in Tagaytay City, Cavite Province.…”
Section: Endolichenic Fungi (Elf) and Their Role In The Lichen Symbiosismentioning
confidence: 99%
See 1 more Smart Citation
“…Thom from Usnea baileyi and a Penicillium sp. from U. bismolliuscula (Santiago et al 2021). The mycelia of P. citrinum isolated from Parmotrema lichens have been shown to contain three antioxidant compounds, with two reported on and determined by Samanthi et al (2015) to be 5′-acetyl-3,5,7′-trimethoxy-3′H-spiro [cyclohexa [2,4]diene-1,1'-isobenzofuran]-3',6-dione and 4-acetyl-2'hydroxy-3',5',6-trimethoxy biphenyl-2-carboxylic acid, and the other reported on and determined by Wickramarachchi et al (2019) to be 10-ethylidene-2,4,9-trimethoxy-10,10a-dihydro-7,11-dioxa-benzo[b] heptalene-6,12-dione; sclerotioramine was not found in that fungal strain.…”
Section: Resultsmentioning
confidence: 98%
“…Endophytic fungi have been isolated from diverse hosts ranging from lichens (Santiago et al 2021), bryophytes (Zhou et al 2015), gymnosperms (De Mesa et al 2020), and angiosperms (Gautam et al 2013;Gautam 2014;General and Guerrero 2017). In the marine environment, endophytic fungi were found in every marine plant, e.g., mangroves (Apurillo et al 2019), algae (Sahoo et al 2021), and seagrasses (Supaphon et al 2017;Ettinger and Eisen 2020).…”
Section: Introductionmentioning
confidence: 99%